Association of Disease Outcome with Diabetes in Lung Cancer Patients - Abid , Amina; Arshad , Ayaz; Arslan , Muhammad (Indus Journal of Bioscience Research, 2025)
Objective: To determine the frequency of diabetes in patients with lung cancer and to compare the frequency of mortality with diabetes in lung cancer patients. Methodology: This study was descriptive case series carried out at department of Medicine, Shaukat Khanum Memorial Cancer Hospital & Research Center Lahore. The duration of the study was six months from January 2024 to June 2024. After meeting selection criteria and applying non-probability convenient sampling 100 patients were enrolled. Informed consent and demographic details were taken. From all the lung cancer patients, history of diabetes was noted. All patients were followed up in medical wards for 3 months. If patient died during treatment, then mortality was labeled as outcome. Results: The mean age of the patients was 50.78±11.57 years and 61% patients were males. Among lung cancer patients 33% were diabetics and mortality during treatment was noted in 46% patients. In diabetics, mortality during treatment was found in 18(54.5%) patients and in non-diabetics it was observed in 28(41.8%) patients (p-value=0.229). Conclusion: This study concluded that one-third of lung cancer patients had diabetes mellitus, and 46% experienced mortality during treatment. Moreover, no statistically significant association was found between the presence of diabetes mellitus and mortality during the treatment of lung cancer patients.